The State of the Art in Philippians Scholarship: Past, Present, and Future - Isaac Douglas Blois; Gregory E. Lamb (Religions, 2024)
This current volume reflects recent research from a wide spectrum of varying perspectives and approaches to Philippians from senior and early career Pauline scholars across the globe [...]